Prognostic value of FDG PET/CT during radiotherapy in head and neck cancer patients - Kim, Suzy (Radiat Oncol J, 2018)
PURPOSE: To evaluate the prognostic value of (18)F-fluorodeoxyglucose positron-emission tomography (FDG PET) with computed tomography (CT) before and during radiotherapy (RT) in patients with head and neck cancer. METHODS: Twenty patients with primary head and neck squamous cell carcinoma were enrolled in this study, of whom 6 had oropharyngeal cancer, 10 had hypopharyngeal cancer, and 4 had laryngeal cancer. Fifteen patients received concurrent cisplatin and 2 received concurrent cetuximab chemotherapy. FDG PET/CT was performed before RT and in the 4th week of RT. The parameters of maximum standardized uptake value, metabolic tumor volume, and total lesion glycolysis (TLG) of the primary tumor were measured, and the prognostic significance of each was analyzed with the Cox proportional hazards model. RESULTS: Higher TLG (>19.0) on FDG PET/CT during RT was a poor prognostic factor for overall survival (OS) (p = 0.001) and progression-free survival (PFS) (p = 0.007). In the multivariate analysis, TLG during RT as a continuous variable was significantly associated with OS and PFS rate (p = 0.023 and p = 0.016, respectively). Tumor response worse than partial remission at 1 month after RT was another independent prognostic factor for PFS (p = 0.024). CONCLUSIONS: Higher TLG of the primary tumor on FDG PET/CT during RT was a poor prognostic factor for OS and PFS in patients with head and neck cancer.